Maize Threshing and Separating Device for Primary Seed Production - A. G. Pastukhov; D. N. Bakharev (Сельскохозяйственные машины и технологии, 2020)
The development of domestic primary maize seed production requires the development of new threshing devices capable to minimize seed grains macro- and microdamage. (Research purpose) To justify the design and technological parameters of the axial-rotary threshing and separating device for varietal and hybrid maize with a device that ensures the cobs orientation in space before threshing and partial violation of their grain structure by friction during swirling by air flow. (Materials and methods) The authors used system analysis methods, ensuring the principle of flow in mechanized lines, building algorithms for the automated systems operation and designing agricultural machines. (Results and discussion) To minimize corn grain damage, the authors recommended the sequence of technological process operations of threshing with an axial-rotary threshing-separating device, into which the cobs were fed in a strictly oriented spatial position with a partially broken grain structure. They improved the orienting- dispensing loading device, presented in the form of a vortex orienting dispenser equipped with an automatic loading level control system. The authors established the design parameters of the vortex orienting batcher based on the experimental determination of the corn cobs mechanical and technological parameters. They proposed methods, equipment and devices for determining the angle of corn cobs repose. The authors calculated the dimensional parameters of the funnel window for the corn cob output and the metering vortex tube diameter. (Conclusions) The authors developed the design of a threshing-separating device with a device for orienting corn cobs in space before threshing and partial violation of their grain structure by friction during swirling by an air stream. They determined the funnel window optimal parameters at the bottom of the vortex orienting batcher: length – 0.378 meters, width – 0.122 meters, vortex tube diameter – at least 0.624 meters.